2022
DOI: 10.3390/economies10020038
|View full text |Cite
|
Sign up to set email alerts
|

Financial Inclusion Indicators Affect Profitability of Jordanian Commercial Banks: Panel Data Analysis

Abstract: Previous literature supports the view that the financial inclusion leads to economic growth and helps alleviate poverty; however, it is still unclear whether financial inclusion increases bank profitability. The study assumes that financial inclusion is significant in enhancing the economy and minimizing loan accounts, and along with this assumption, the deposit size decreases the Jordanian banks’ profitability despite the fact that the financial services and access to them have no significant influence upon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…The findings of these studies showed the significant impact of financial inclusion in enhancing a bank's profit. However, the related studies highlighted that the relationship between financial inclusion and bank profitability is unclear as it depends on the different measurements of financial inclusion (Issaka Jajah et al, 2020;Kumar et al, 2022;Al-eitan et al, 2022). In contrast, this present study measures financial inclusion with the three dimensions of access, availability, and usage, following Erlando et al (2020).…”
Section: Journal Ofmentioning
confidence: 84%
See 2 more Smart Citations
“…The findings of these studies showed the significant impact of financial inclusion in enhancing a bank's profit. However, the related studies highlighted that the relationship between financial inclusion and bank profitability is unclear as it depends on the different measurements of financial inclusion (Issaka Jajah et al, 2020;Kumar et al, 2022;Al-eitan et al, 2022). In contrast, this present study measures financial inclusion with the three dimensions of access, availability, and usage, following Erlando et al (2020).…”
Section: Journal Ofmentioning
confidence: 84%
“…Furthermore, previous studies have focused on determining the impact of financial inclusion on bank profitability, such as Al-eitan et al (2022) and Shihadeh et al (2018), which conducted a study in Jordan, Issaka Jajah et al (2020) in Sub Sub-Saharan Africa, and Kumar et al (2022) in Japan. The findings of these studies showed the significant impact of financial inclusion in enhancing a bank's profit.…”
Section: Journal Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the total assets' logarithm was applied to estimate the size of the bank. The results of their study differed a lot -some of them believed the bank size hurt the profitability [12], and some of them believed the size has a beneficial influence on profitability.…”
Section: Explanatory Variablesmentioning
confidence: 96%
“…Several studies were carried out analyzing and comparing the determinants of financial inclusion among regions (Sarma & Pais, 2011;Gupte et al, 2012;Akudugu, 2013;Hassan, 2015;Park & Mercado, 2015;Lotto, 2016;Hillary, 2016;Uddin et al, 2017;Abel et al, 2018;Hussaini & Chibuzo, 2018;Neaime and Gaysset, 2018;Anyanwu et al, 2018;Mdasha et al, 2018;Ojwang & Otinga, 2019;Kapaya, 2019;Kinyua & Omagwa, 2020;Al-Chahadah et al, 2020;Koomson et al, 2020;Singh, 2020;Anastesia et al, 2020;Kamal, 2021;Eze & Alugbuo, 2021;Johnpaul & Patience, 2021;Maity & Sahu, 2021;Naser & Alabassi, 2022;Al-Eitan et al, 2022;Winful et al, 2022). However, most of the previous studies focused on the determinants of financial inclusion in the developing countries of Asia, South America, Europe, North Africa, Sub-Saharan Africa or in countries such as Bangladesh, India, China and Indonesia.…”
Section: Introductionmentioning
confidence: 99%